Addressing treatment capacity of uninsured adults with co-occurring disorders. Issue 3 (30th June 2020) - Gruber, Kenneth J.; Poole, Kelly Jay; Graves, Kelly N.; Richburg, Antonia Monk
Abstract : Purpose: The purpose of this paper is to report on the success of an initiative involving the transformation of a group of small substance use treatment only or mental health treatment only provider agencies serving uninsured adults into providers of co-occurring disorder treatment. Design/methodology/approach: The paper uses a case study narrative to describe the initiative and the transformation of the participant agencies from being providers of mental health or substance use treatment to providers of co-occurring disorders. Findings: Six agencies serving uninsured adults expanded their scope of patient treatment services to include the capacity to treat adults with co-occurring disorders. This was achieved with modest support funding from a local foundation. The initiative has been ongoing for five years. Practical implications: The outcome of this initiative demonstrates the financial and practical feasibility of improving and expanding treatment services to low-resourced patient populations. The participating agencies were able to improve their capacity to treat patients with substance use or mental health issues that previously they were not prepared to treat and thus increased their ability to provide integrated care. Originality/value: The initiative described here shows that the treatment of concomitant substance use and mental health disorders is within the range of many small-scale treatment providers, if provided the leadership and support. Delivery of effective treatments to populations experiencing co-occurring disorders that are underserved and undertreated are achievable in community-based clinical practices. This has implications for developing treatment capacity outside of hospital settings to enable treatment of co-occurring disorders to become more accessible.